Pleasure-Seeking Or Fear-Driven? A Conceptual Examination Of Hedonic Motivation And FOMO As Catalysts Of Impulsive Buying In E-Commerce - Auliya Allendifa; Muhammad Dharma Tuah Putra Nasution; Fadli Fadli (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Although impulsive buying in e-commerce has received considerable scholarly attention, the psychological mechanisms through which digitally engineered platform environments systematically erode consumer self-regulation remain undertheorized. This paper advances the Affective Urgency Model, a conceptual framework grounded in the Stimulus-Organism-Response paradigm, dual-process theory, prospect theory, approach-avoidance motivation theory, and self-determination theory. Through a critical narrative synthesis of Scopus and Web of Science literature, three theoretical contributions are made. First, hedonic motivation is reframed as an affective override mechanism that activates System 1 processing and suppresses deliberative evaluation, rendering consumers structurally vulnerable to spontaneous purchases. Second, commercially induced FOMO is reconceptualized as a threat response driven by loss aversion, wherein platform-deployed scarcity stimuli frame purchase inaction as loss and compress the decision window. Third, the construct of affective urgency is introduced to capture the compounded state arising from the co-activation of approach motivation and avoidance motivation, amplifying impulsive buying beyond the additive effects of either variable independently. The framework also incorporates the post-purchase paradox, wherein affective urgency-driven purchases produce cognitive dissonance, regret, and financial well-being deterioration despite their immediate hedonic appeal. Three formal propositions and a research agenda for empirical validation are advanced.